Coating composition, anti-fogging product and preparation method thereof
By using the inorganic hydrophilic coating prepared by low-melting point glass powder and inorganic nanomaterial composition, the problem that traditional anti-fogging coatings are difficult to have high mechanical properties and high light transmittance is solved, and high efficiency anti-fogging effect and good light transmittance are achieved.
Patent Information
- Application Number
- CN202411819177.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional hydrophilic anti-fogging coatings are difficult to have high mechanical properties and high light transmittance, and the anti-fogging effect of some inorganic coatings is harsh, affecting the use of transparent substrates.
Using a low-melting point glass powder and inorganic nanomaterial composition with a mass ratio of 1: (1~5), the low-melting point glass powder is melted and bonded to the inorganic nanomaterial at high temperature to form an inorganic hydrophilic coating, which improves the hardness and scratch resistance of the coating while maintaining high light transmittance.
The anti-fogging coating has high mechanical properties and high light transmittance, solving the problems of poor hardness and harsh triggering conditions of traditional coatings.
Smart Images

Figure CN119775805A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and in particular to a coating composition, an anti-fogging product and a preparation method thereof. Background Art
[0002] Transparent substrates such as glass have excellent optical properties and their high transmittance makes them widely used in daily life. However, in some environments where transparent substrates are used, due to temperature changes, water vapor will liquefy into water droplets on the surface of the substrate, generating fog, causing a sharp drop in transparency and visibility, affecting the use of the substrate. Therefore, it is of great practical value to study a transparent substrate with anti-fog effect.
[0003] In traditional technology, the surface temperature of the substrate is made higher than the dew point temperature of the fog by heating, thereby reducing the condensation of fog and achieving the anti-fog effect. However, this method requires a specific heating device and generates additional energy consumption, which limits its application. Another traditional technology adjusts the affinity between the substrate and water droplets by forming a hydrophilic functional coating on the surface of the substrate, thereby achieving the anti-fog effect. However, the current hydrophilic functional coating still has the following problems: it is difficult to have both high mechanical properties and high light transmittance. Summary of the invention
[0004] Based on this, one aspect of the present application provides a coating composition that can be used to prepare an anti-fogging coating with both high mechanical properties and high light transmittance.
[0005] In addition, another aspect of the present application provides an anti-fogging product and a preparation method thereof.
[0006] A coating composition comprising a low-melting-point glass powder and an inorganic nanomaterial in a mass ratio of 1:(1-5);
[0007] Wherein, the melting temperature of the low-melting-point glass powder is less than or equal to 650°C.
[0008] Optionally, the low-melting-point glass powder includes one or more of lead-based low-melting-point glass powder, sodium borate low-melting-point glass powder, potassium aluminum silicate low-melting-point glass powder, calcium zincate low-melting-point glass powder and phosphate-type low-melting-point glass powder.
[0009] Optionally, the inorganic nanomaterial includes one or more of solid silica nanoparticles, mesoporous silica nanoparticles, hollow silica nanospheres, silica nanosheets and diatomaceous earth.
[0010] Optionally, the mass ratio of the low-melting point glass powder to the inorganic nanomaterial is 1:(2-4).
[0011] Optionally, the average particle sizes of the low-melting-point glass powder and the inorganic nanomaterial are respectively 20 nm to 1000 nm.
[0012] Optionally, an anti-settling agent and a solvent are also included. Calculated by mass percentage, the coating composition includes: 2% to 5% low-melting point glass powder, 2% to 10% inorganic nanomaterials, 0.5% to 2% anti-settling agent and 83% to 95.5% solvent.
[0013] Optionally, the anti-settling agent includes one or more of fatty alcohol polyoxyethylene ether sulfate, polyvinyl alcohol and polyacrylamide.
[0014] Optionally, the solvent comprises water.
[0015] An anti-fogging product comprises a transparent substrate and an anti-fogging coating disposed on the surface of the transparent substrate, wherein the material for preparing the anti-fogging coating comprises a low-melting-point glass material and an inorganic nanomaterial in a mass ratio of 1:(1-5);
[0016] Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
[0017] Optionally, the transparent substrate comprises glass.
[0018] Optionally, the melting temperature of the low-melting-point glass material is lower than the softening temperature of the glass;
[0019] Optionally, the low melting point glass material includes one or more of a lead-based low melting point glass material, a sodium borate low melting point glass material, a potassium aluminum silicate low melting point glass material, a calcium zincate low melting point glass material and a phosphate-based low melting point glass material.
[0020] Optionally, the inorganic nanomaterial includes one or more of solid silica nanoparticles, mesoporous silica nanoparticles, hollow silica nanospheres, silica nanosheets and diatomaceous earth.
[0021] Optionally, the mass ratio of the low-melting point glass material to the inorganic nanomaterial is 1:(2-4).
[0022] Optionally, the anti-fogging article comprises a shower room glass or a bathroom mirror.
[0023] A method for preparing an anti-fogging product comprises the following steps:
[0024] Forming an anti-fogging coating on the surface of a transparent substrate to prepare an anti-fogging product;
[0025] Wherein, the material for preparing the anti-fogging coating comprises a low-melting-point glass material and an inorganic nanomaterial in a mass ratio of 1: (1-5);
[0026] Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
[0027] Optionally, the step of forming an anti-fogging coating on the surface of the transparent substrate comprises:
[0028] Obtaining a coating composition, wherein the coating composition comprises, by mass percentage, 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of an anti-settling agent, and 83% to 95.5% of a solvent;
[0029] The coating composition is applied on the surface of the transparent substrate, the solvent is removed by heating and the low-melting-point glass powder is melted, and the anti-fogging coating is formed on the surface of the transparent substrate after cooling.
[0030] Optionally, in the step of melting the low-melting-point glass powder, the temperature is 500° C. to 700° C. and the time is 10 min to 60 min.
[0031] Optionally, before the step of forming the anti-fogging coating on the surface of the transparent substrate, the method further includes: performing a surface hydroxylation treatment on the transparent substrate.
[0032] The coating composition provided in the present application includes low-melting-point glass powder and inorganic nanomaterials in a mass ratio of 1: (1-5). The low-melting-point glass powder is used as a binder to melt and bond the inorganic nanomaterials with hydrophilic function at high temperature to form an inorganic hydrophilic coating. Compared with the organic hydrophilic coating, the mechanical properties such as hardness and scratch resistance are improved. The low-melting-point glass powder has good light transmittance, and the inorganic nanomaterial is nanometer-level, which has little effect on light transmittance. Therefore, the above-mentioned coating composition is applied to the surface of a transparent substrate, which has little effect on the light transmittance of the transparent substrate, so that the prepared anti-fogging coating can have both good mechanical properties and high light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 A schematic diagram of a process flow of a method for preparing an anti-fogging product according to some embodiments of the present application;
[0035] Figure 2 This is a test graph of the water contact angle of the anti-fogging product prepared in Example 1 of the present application;
[0036] Figure 3 This is a test chart of the anti-fogging performance of the anti-fogging product prepared in Example 1 of the present application;
[0037] Figure 4This is a test graph of the water contact angle of the anti-fogging product prepared in Example 2 of the present application;
[0038] Figure 5 This is a test chart of the anti-fogging performance of the anti-fogging product prepared in Example 2 of the present application;
[0039] Figure 6 This is a test chart of the anti-fogging performance of the anti-fogging product prepared in Example 3 of the present application;
[0040] Figure 7 This is a test diagram of the water contact angle of the anti-fogging product prepared in Comparative Example 1 of the present application;
[0041] Figure 8 This is a test chart of the anti-fogging performance of the anti-fogging product prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the specific embodiments. The preferred embodiments of the present application are provided in the specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0045] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0046] In the description of the present application, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.
[0047] In this application, "one or several" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0048] In this application, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0049] In this document, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent technical solutions are related in terms of the content covered, but should not be understood as a limitation on the previous technical solution, nor can it be understood as a limitation on the protection scope of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0050] Herein, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" item is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist, or means that component X is contained or not contained.
[0051] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.
[0052] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0053] The terms "including" and "having" and any variations thereof in the embodiments of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.
[0054] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.
[0055] The first aspect of the present application provides a coating composition, comprising: a low-melting-point glass powder and an inorganic nanomaterial in a mass ratio of 1:(1-5);
[0056] The melting temperature of the low-melting-point glass powder is less than or equal to 650°C.
[0057] The present application has found that the traditional hydrophilic anti-fogging coating is usually an organic coating, and the mechanical properties of the organic coating, such as hardness and scratch resistance, are poor, so it is necessary to improve its cross-linking degree, but the increase in cross-linking degree will lead to a significant decrease in light transmittance. The above-mentioned coating composition provided in the present application includes a low-melting point glass powder and an inorganic nanomaterial in a mass ratio of 1: (1~5). The low-melting point glass powder is used as a binder, and the inorganic nanomaterial with a hydrophilic function is melted and bonded at a high temperature to form an inorganic hydrophilic coating. Compared with the organic hydrophilic coating, the mechanical properties such as hardness and scratch resistance are improved. In addition, the low-melting point glass powder has good light transmittance, and the inorganic nanomaterial is nanometer-level, which has little effect on light transmittance. Therefore, the above-mentioned coating composition is applied to the surface of a transparent substrate, which has little effect on the light transmittance of the transparent substrate, so that the prepared anti-fogging coating can have both good mechanical properties and high light transmittance.
[0058] In addition, there are some inorganic substances with hydrophilic effect such as titanium oxide used on the surface of transparent substrates in traditional technology, but they are photosensitive materials and require ultraviolet irradiation to exert super hydrophilic effect. Moreover, the reflectivity of such inorganic substances is high, which easily leads to a decrease in the light transmittance of transparent substrates. The above-mentioned coating composition provided by the present application is matched with inorganic nanomaterials and low-melting-point glass powder. The inorganic nanomaterials used are rich in hydrophilic groups or hydrophilic structures such as microporous structures. Under normal conditions, they can be infiltrated with water vapor and exert super hydrophilic effect without light exposure, which solves the problem that the anti-fog effect of traditional inorganic coatings has harsh triggering conditions and a large impact on light transmittance.
[0059] Therefore, the above-mentioned coating composition includes low-melting point glass powder and inorganic nanomaterials in a mass ratio of 1: (1~5). Through high-temperature burning of the low-melting point glass powder, the inorganic nanomaterials with hydrophilic function are bonded and retained on the surface of the substrate in a melting-solidification manner, which effectively solves the problems of poor coating hardness and scratch resistance of the current hydrophilic functional coatings and the harsh triggering conditions of the anti-fog effect of some inorganic coatings, while ensuring a high light transmittance.
[0060] Low melting point glass powder is a material different from ordinary glass powder. It has a low melting temperature and is also called low temperature melting glass powder. The two have the same meaning and can be mixed.
[0061] In some embodiments, the low melting point glass powder includes one or more of lead-based low-temperature melting glass powder, sodium borate low-temperature melting glass powder, potassium aluminum silicate low-temperature melting glass powder, calcium zincate low-temperature melting glass powder and phosphate-type low-temperature melting glass powder.
[0062] In some embodiments, the melting temperature of the low-melting glass powder is less than or equal to 650° C. Generally, the softening temperature of glass is about 650° C. to 680° C. The melting temperature of the low-melting glass powder is within the above range, so that when the low-melting glass powder is used to prepare an anti-fogging coating on glass, the glass does not soften.
[0063] In some embodiments, the inorganic nanomaterial includes one or more of solid silica nanoparticles, mesoporous silica nanoparticles, hollow silica nanospheres, silica nanosheets, and diatomaceous earth.
[0064] The mass ratio of low-melting-point glass powder to inorganic nanomaterials is 1: (1-5). If the proportion of low-melting-point glass powder is too small, the adhesion is poor; if the proportion of low-melting-point glass powder is too large, it will wrap the inorganic nanomaterials, making it unable to exert its hydrophilic effect and thus affecting the anti-fogging effect. If the proportion of inorganic nanomaterials is too small, the hydrophilic effect is poor and affects the anti-fogging effect; if the proportion of inorganic nanomaterials is too large, since they have no adhesion, the adhesion effect is poor, which also leads to a decrease in the hydrophilic effect.
[0065] Exemplarily, the mass ratio of the low melting point glass powder to the inorganic nano material can be, but is not limited to, 1:1, 1:1.3, 1:1.5, 1:1.6, 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.5, 1:5, or a range consisting of any two of these values. In some of the embodiments, the mass ratio of the low melting point glass powder to the inorganic nano material is 1:(1-4). In some of the embodiments, the mass ratio of the low melting point glass powder to the inorganic nano material is 1:(2-4).
[0066] In some embodiments, the average particle size of the low melting point glass powder and the inorganic nano material is 20nm~1000nm respectively. For example, the average particle size can be but not limited to 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or a range consisting of any two of these values. It is understood that the average particle size of the low melting point glass powder and the inorganic nano material can be the same or different, and there is no special limitation. Optionally, the average particle size of the low melting point glass powder and the inorganic nano material is 50nm~100nm respectively.
[0067] In some embodiments, the coating composition further includes an anti-settling agent and a solvent.
[0068] Specifically, the coating composition includes, by mass percentage, 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of an anti-settling agent, and 83% to 95.5% of a solvent.
[0069] In a specific example, in the coating composition, the mass percentage of the low melting point glass powder can be, but is not limited to, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of these values.
[0070] In a specific example, in the coating composition, the mass percentage of the inorganic nanomaterial can be, but is not limited to, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of these values.
[0071] In a specific example, in the coating composition, the mass percentage of the anti-settling agent can be, but is not limited to, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2% or a range consisting of any two of these values.
[0072] In a specific example, in the coating composition, the mass percentage of the solvent can be, but is not limited to, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 95.5% or a range consisting of any two of these values.
[0073] In some embodiments, the anti-settling agent includes one or more of fatty alcohol polyoxyethylene ether sulfate, polyvinyl alcohol and polyacrylamide. Adding the anti-settling agent to the coating composition is beneficial to improving the dispersibility of the low-melting point glass powder and the inorganic nanomaterial in the solvent, making them less likely to settle, and thus facilitating application on the surface of the transparent substrate by spraying to form a coating.
[0074] In some embodiments, the solvent includes water. Inorganic nanomaterials have better dispersibility in water, and the solvent including water is beneficial to improving the dispersibility of the coating composition.
[0075] The second aspect of the present application provides an anti-fogging product, comprising a transparent substrate and an anti-fogging coating disposed on the surface of the transparent substrate, wherein the material for preparing the anti-fogging coating comprises a low-melting-point glass material and an inorganic nanomaterial in a mass ratio of 1: (1-5);
[0076] Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
[0077] The specific low-melting-point glass material is a material obtained by melting and solidifying the aforementioned low-melting-point glass powder, and its composition is the same as that of the aforementioned low-melting-point glass powder. The specific inorganic nanomaterial is as described in the first aspect above, and will not be repeated here.
[0078] In some embodiments, the transparent substrate includes glass. For example, the transparent substrate is tempered glass. Specifically, the melting temperature of the low-melting-point glass material is lower than the softening temperature of the glass. Through the above arrangement, the glass does not soften during the melting process of the low-melting-point glass powder.
[0079] In some embodiments, the anti-fogging article comprises a shower glass or a bathroom mirror.
[0080] In some embodiments, the thickness of the anti-fogging coating is less than 1 μm. It is understood that in the present application, "less than" includes the number, for example, the thickness less than 1 μm means the thickness is less than or equal to 1 μm.
[0081] In some embodiments, the water contact angle of the anti-fogging coating is less than or equal to 10°. The anti-fogging coating has excellent hydrophilicity, which is beneficial to improving its anti-fogging effect.
[0082] In some embodiments, before and after the anti-fogging coating is applied on the surface of the transparent substrate, the change in light transmittance is less than or equal to 10%, and further less than or equal to 8%. Before and after the anti-fogging coating is applied on the surface of the transparent substrate, the change in light transmittance is small, and the impact on the transparent substrate is small.
[0083] The third aspect of the present application provides a method for preparing an anti-fogging product, comprising the following steps:
[0084] Forming an anti-fogging coating on the surface of a transparent substrate to prepare an anti-fogging product;
[0085] The materials for preparing the anti-fogging coating include low-melting-point glass material and inorganic nanomaterial in a mass ratio of 1: (1-5);
[0086] Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
[0087] In some embodiments, the step of forming an anti-fogging coating on the surface of the substrate comprises:
[0088] Obtaining a coating composition, which comprises, by mass percentage, 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of an anti-settling agent, and 83% to 95.5% of a solvent;
[0089] The coating composition is applied on the surface of a transparent substrate, heated to remove the solvent and melt the low-melting-point glass powder, and then cooled to form an anti-fogging coating on the surface of the transparent substrate.
[0090] In some embodiments, the step of applying the coating composition on the surface of the transparent substrate is carried out by spraying. Exemplarily, the coating composition is placed in an atomizing device and sprayed on the surface of the transparent substrate.
[0091] In some embodiments, in the step of melting the low-melting-point glass powder, the temperature is 500-700°C and the time is 10-60 minutes. For example, the heating temperature may be, but is not limited to, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 700°C or a range consisting of any two of these values. The heating time may be, but is not limited to, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes or a range consisting of any two of these values. In a specific example, the step of melting the low-melting-point glass powder is carried out in a high-temperature furnace.
[0092] In some embodiments, after the cooling step, washing and drying steps are also included. Specifically, washing with deionized water is used and then drying is performed.
[0093] In some embodiments, before the step of forming an anti-fogging coating on the surface of the transparent substrate, the step further includes: performing a surface hydroxylation treatment on the transparent substrate. The surface hydroxylation treatment enhances the adhesion of the anti-fogging coating. In one specific example, the surface hydroxylation treatment of the transparent substrate is performed by plasma treatment. It is understood that the surface hydroxylation treatment is not limited to plasma treatment, but may also be other methods commonly used in the art.
[0094] In some embodiments, before the step of performing surface hydroxylation treatment on the transparent substrate, the method further includes: performing degreasing treatment and liquid droplet removal treatment on the transparent substrate.
[0095] Specifically, the step of removing oil stains includes: placing the transparent substrate in an ethanol-water solution with a mass ratio of 1:1 and ultrasonically treating it for 10 minutes. The oil stains on the surface of the transparent substrate are removed by the above treatment. The step of removing droplets includes: using an air gun to blow away droplets on the surface of the transparent substrate.
[0096] Specifically, before the step of forming an anti-fogging coating on the surface of the transparent substrate, the method further includes:
[0097] The transparent substrate was placed in an ethanol-water solution with a mass ratio of 1:1 and subjected to ultrasonic treatment for 10 min;
[0098] Use an air gun to blow away droplets on the surface of the transparent substrate;
[0099] The transparent substrate is subjected to surface hydroxylation treatment.
[0100] In some of these examples, see Figure 1 The preparation method of the anti-fogging product comprises the following steps:
[0101] Step S110: performing surface hydroxylation treatment on the transparent substrate.
[0102] Step S120: obtaining a coating composition, which comprises, by mass percentage, 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of an anti-settling agent, and 83% to 95.5% of a solvent.
[0103] Step S130: applying the coating composition on the surface of the transparent substrate, heating to remove the solvent and melt the low-melting-point glass powder, and forming an anti-fogging coating on the surface of the transparent substrate after cooling to prepare an anti-fogging product.
[0104] The preparation method of the above-mentioned anti-fogging product is to bond the inorganic nanomaterial with hydrophilic function to the surface of the transparent substrate in a melting-solidification manner through high-temperature calcination of low-melting-point glass powder, thereby forming an inorganic hydrophilic coating, which effectively solves the problems of poor coating hardness and scratch resistance of the current hydrophilic functional coating and the harsh conditions for triggering the anti-fog effect of some inorganic coatings.
[0105] Figure 1 This is a schematic diagram of a method for preparing an anti-fogging product according to an embodiment of the present invention. It should be understood that although Figure 1 The steps in the flowchart are shown in sequence as indicated by the arrows, but these steps are not necessarily performed in the order indicated by the arrows. Unless otherwise specified in this document, there is no strict order restriction for the execution of these steps, and they can be performed in other orders. Figure 1At least part of the steps may include multiple sub-steps or multiple stages. These sub-steps or stages are not necessarily executed at the same time, but can be executed at different times. The order of execution is not necessarily sequential, but can be executed in turn or alternately with other steps or at least part of other sub-steps or stages.
[0106] In order to make the purpose and advantages of the present application clearer, the coating composition, anti-fogging products and their effects of the present application are further described in detail in conjunction with specific examples. It should be understood that the specific examples described herein are only used to explain the present application and shall not be used to limit the present application. The following examples do not include other components except for unavoidable impurities unless otherwise specified. The drugs and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature and books or the methods recommended by the manufacturer.
[0107] The raw materials used in the following examples and comparative examples are as follows:
[0108] The melting temperature of potassium aluminum silicate low-temperature melting glass powder is 450°C, the melting temperature of calcium zincate type low-temperature melting glass powder is 400°C, the melting temperature of phosphate type low-temperature melting glass powder is 330°C, and the melting temperature of sodium borate type low-temperature melting glass powder is 550°C; the average particle size of solid silica nanoparticles is 20nm~30nm, purchased from Zhejiang Zhiti Nanowei New Materials Co., Ltd., and the average particle size of mesoporous silica nanoparticles is 30nm~50nm, purchased from Beijing Zhongke Yannuo New Materials Technology Co., Ltd.
[0109] Example 1
[0110] The present embodiment provides a coating composition, which comprises, by mass percentage, 2% potassium aluminum silicate low-temperature melting glass powder, 5% solid silicon dioxide nanoparticles, 1% polyvinyl alcohol and 92% deionized water.
[0111] This embodiment also provides an anti-fogging product, comprising tempered glass and an anti-fogging coating disposed on the surface of the tempered glass, wherein the material for preparing the anti-fogging coating comprises a potassium aluminum silicate low-temperature melting glass material and solid silicon dioxide nanoparticles in a mass ratio of 1:2.5, and the thickness is 50nm to 60nm. The steps for preparing the anti-fogging product of this embodiment are as follows:
[0112] The above coating composition was mixed and mechanically stirred for 30 minutes, sprayed on the surface of the tempered glass after plasma treatment through an atomizing device, dried and dehydrated, placed in a high-temperature furnace, and treated at 570°C for 1 hour. After cooling to room temperature, the tempered glass was taken out, and the surface of the tempered glass was washed with deionized water and dried to obtain a tempered glass with an anti-fogging coating, i.e., the anti-fogging product of this embodiment.
[0113] Example 2
[0114] The present embodiment provides a coating composition, which comprises, by mass percentage, 2% calcium zincate type low-temperature melting glass powder, 5% mesoporous silica nanoparticles, 1% polyvinyl alcohol and 92% deionized water.
[0115] This embodiment also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In this embodiment, the material for preparing the anti-fogging coating includes a calcium zincate type low-temperature melting glass material and mesoporous silica nanoparticles in a mass ratio of 1:2.5.
[0116] The preparation steps of the anti-fogging product of this embodiment are the same as those of embodiment 1, and will not be repeated. It can be understood that in the actual preparation process, the construction temperature used can be adjusted according to the different low-melting glass powders, and the construction temperature should be higher than the initial melting temperature of the low-melting glass powder.
[0117] Example 3
[0118] The present embodiment provides a coating composition, which comprises, by mass percentage, 2% phosphate-type low-temperature melting glass powder, 7% mesoporous silica nanoparticles, 1% polyacrylamide and 90% deionized water.
[0119] This embodiment also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In this embodiment, the material for preparing the anti-fogging coating includes a phosphate-type low-temperature melting glass material and mesoporous silica nanoparticles in a mass ratio of 1:3.5.
[0120] The preparation steps of the anti-fogging product of this embodiment are the same as those of Embodiment 1 and will not be repeated herein.
[0121] Example 4
[0122] The present embodiment provides a coating composition, which comprises, by mass percentage, 3% sodium borate type low-temperature melting glass powder, 6.5% mesoporous silica nanoparticles, 0.5% sodium fatty alcohol polyoxyethylene ether sulfate, and 90% deionized water.
[0123] This embodiment also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In this embodiment, the material for preparing the anti-fogging coating includes a sodium borate type low-temperature melting glass material and mesoporous silica nanoparticles in a mass ratio of 1:2.2.
[0124] The preparation steps of the anti-fogging product of this embodiment are the same as those of Embodiment 1 and will not be repeated herein.
[0125] Example 5
[0126] This embodiment provides a coating composition, which includes, by mass percentage, 5% calcium zincate type low-temperature melting glass powder, 10% solid silicon dioxide nanoparticles, 2% fatty alcohol polyoxyethylene ether sodium sulfate, and 83% deionized water.
[0127] This embodiment also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In this embodiment, the material for preparing the anti-fogging coating includes a calcium zincate type low-temperature melting glass material and solid silicon dioxide nanoparticles in a mass ratio of 1:2.
[0128] The preparation steps of the anti-fogging product of this embodiment are the same as those of Embodiment 1 and will not be repeated herein.
[0129] Example 6
[0130] This embodiment provides a coating composition, which includes, by mass percentage, 2% phosphate-type low-temperature glass powder, 2% diatomaceous earth, 0.5% sodium fatty alcohol polyoxyethylene ether sulfate, and 95.5% deionized water.
[0131] This embodiment also provides an anti-fogging product, which is similar to the anti-fogging product of embodiment 1, except that the composition of the anti-fogging coating is different. In this embodiment, the material for preparing the anti-fogging coating includes a phosphate-type low-temperature melting glass material and diatomaceous earth in a mass ratio of 1:1.
[0132] The preparation steps of the anti-fogging product of this embodiment are the same as those of Embodiment 1 and will not be repeated herein.
[0133] Comparative Example 1
[0134] Comparative Example 1 provides a blank tempered glass without a coating, which is the same as the tempered glass used in Example 1.
[0135] Comparative Example 2
[0136] Comparative Example 2 provides a coating composition, which includes, by mass percentage, 12% sodium borate type low-temperature melting glass powder, 6.5% mesoporous silica nanoparticles, 0.5% polyvinyl alcohol and 81% deionized water.
[0137] Comparative Example 2 also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In Comparative Example 2, the material for preparing the anti-fogging coating includes a sodium borate type low-temperature melting glass material and mesoporous silica nanoparticles in a mass ratio of 1:0.54.
[0138] The preparation steps of the anti-fogging product of Comparative Example 2 are the same as those of Example 1 and will not be repeated herein.
[0139] Comparative Example 3
[0140] Comparative Example 3 provides a coating composition, which includes, by mass percentage, 2% phosphate-type low-temperature glass powder, 12% solid silica nanoparticles, 0.5% sodium fatty alcohol polyoxyethylene ether sulfate, and 85.5% deionized water.
[0141] Comparative Example 3 also provides an anti-fogging product, which is similar to the anti-fogging product of Example 1, except that the material composition of the anti-fogging coating is different. In Comparative Example 3, the material for preparing the anti-fogging coating includes a phosphate-type low-temperature melting glass material and solid silica nanoparticles in a mass ratio of 1:6.
[0142] The preparation steps of the anti-fogging product of Comparative Example 3 are the same as those of Example 1 and will not be repeated herein.
[0143] The following is the test part:
[0144] (1) Anti-fogging performance test: 40 mL of hot water at 70°C was placed in a transparent plastic cup or glass cup, and the anti-fogging products prepared in the above embodiments and comparative examples or blank tempered glass were placed on the transparent plastic cup or glass cup to observe whether the surface of the material fogged within 3 minutes.
[0145] (2) Water contact angle test: a drop of deionized water was dropped on the anti-fogging coating of the anti-fogging product prepared in each embodiment and comparative example or on the surface of blank tempered glass. After the drop was stable, the contact angle was measured by using a contact angle meter and image analysis.
[0146] (3) Abrasion resistance test: The anti-fogging products or blank tempered glass prepared in each embodiment and comparative example were placed on an abrasion resistance tester and fixed, and abrasion resistance test was performed using a scouring pad. The weight of the load block was 500 g, and the friction area was 3 cm×8 cm. The friction process was stopped after 3000 times of wet grinding with water. The anti-fogging performance and water contact angle of the anti-fogging products or blank tempered glass prepared in each embodiment and comparative example were tested according to the above method.
[0147] (4) Transmittance test: Use a Tri-NIT optical transmittance meter to test the transmittance. Place the anti-fogging product or blank tempered glass to be tested on the sample rack and adjust it to a suitable position to ensure that the surface is clean and free of dirt. Adjust the instrument parameters and start measuring. Keep the environment stable during the test to avoid external interference. After the test is completed, the instrument automatically displays the transmittance results and related data.
[0148] The test performances of the anti-fogging products or blank tempered glass prepared in the above embodiments and comparative examples are shown in Table 1 below.
[0149] Table 1
[0150]
[0151] Figure 2 This is a test diagram of the water contact angle of the anti-fogging coating in the anti-fogging product prepared in Example 1. Figure 3 This is a test diagram of the anti-fogging performance of the anti-fogging product prepared in Example 1. Figure 2 In the figure, CA left: 8.9 means the water contact angle on the left is 8.9°, and CA right: 8.8 means the water contact angle on the right is 8.8°. Figure 2 and Figure 3 It can be seen that the water contact angle of the anti-fogging coating of the anti-fogging product prepared in Example 1 is less than 10°, and no fogging occurs within the 3-min test time, indicating good anti-fogging performance. Figure 4 This is a test diagram of the water contact angle of the anti-fogging coating of the anti-fogging product prepared in Example 2. Figure 5 This is a test diagram of the anti-fogging performance of the anti-fogging product prepared in Example 2. Figure 4 In the figure, CA left: 6.4 means the water contact angle on the left is 6.4°, and CA right: 5.9 means the water contact angle on the right is 5.9°. Figure 4 and Figure 5 It can be seen that the water contact angle of the anti-fogging coating prepared in Example 2 is less than 10°, and no fogging occurs within the 3-minute test time, indicating good anti-fogging performance. The water contact angle of the anti-fogging coating of the anti-fogging product prepared in Example 3 is less than 5°, and the water contact angle is too small to be measured by laboratory instruments. Therefore, the water contact angle test diagram is not given. Figure 6 This is a test chart of the anti-fogging performance of the anti-fogging product prepared in Example 3. Figure 6 It can be seen that the anti-fogging coating prepared in Example 3 did not fog within the 3-minute test time, and the anti-fogging performance was good. The anti-fogging performance of Examples 4 to 6 is similar to that of Examples 1 to 3, and the relevant test graphs are not repeated here.
[0152] Figure 7 This is a test diagram of the water contact angle of the blank tempered glass of Comparative Example 1. Figure 8This is a test diagram of the anti-fog performance of the blank tempered glass of Comparative Example 1. Figure 7 In the figure, CA left: 29.8 means the water contact angle on the left is 29.8°, and CA right: 28.8 means the water contact angle on the right is 28.8°. Figure 7 and Figure 8 It can be seen that the water contact angle of the blank tempered glass of Comparative Example 1 is about 30°, and fogging is obvious within the 3-min test time, and the glass does not have anti-fogging performance.
[0153] It can be seen from Table 1 that the anti-fogging products of Examples 1 to 6 have good anti-fogging effects, with water contact angles <10°, and further, water contact angles <5°, and after a certain wear test, the water contact angles are still <10°, and have excellent mechanical properties. In addition, it can also be seen from Table 1 that after the anti-fogging coating is applied to the surface of the tempered glass, the change in light transmittance is less than or equal to 10%, and further less than or equal to 8% relative to the blank tempered glass, and the light transmittance is less affected.
[0154] In Comparative Examples 2 to 3, the mass ratio of the low-melting-point glass powder and the inorganic nanomaterial is not appropriate, and the prepared anti-fogging coating has poor anti-fogging effect and low light transmittance (such as Comparative Example 2), or has an anti-fogging effect, but after a wear resistance test, the water contact angle increases and there is no anti-fogging effect (such as Comparative Example 3).
[0155] Therefore, in some embodiments of the present application, by providing an inorganic hydrophilic coating of low-melting-point glass material and inorganic nanomaterial in a mass ratio of 1: (1-5) on the surface of the transparent substrate, it is beneficial to improve its anti-fog effect, reduce the water contact angle, and improve the wear resistance. At the same time, the light transmittance of the transparent substrate surface is less affected.
[0156] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0157] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.
Claims
1. A coating composition, characterized in that It includes low melting point glass powder and inorganic nanomaterials in a mass ratio of 1: (1-5); Wherein, the melting temperature of the low-melting-point glass powder is less than or equal to 650°C.
2. The coating composition according to claim 1, characterized in that The low melting point glass powder includes one or more of lead-based low melting point glass powder, sodium borate low melting point glass powder, potassium aluminum silicate low melting point glass powder, calcium zincate low melting point glass powder and phosphate-based low melting point glass powder.
3. The coating composition according to claim 1, characterized in that The inorganic nanomaterials include one or more of solid silica nanoparticles, mesoporous silica nanoparticles, hollow silica nanospheres, silica nanosheets and diatomaceous earth.
4. The coating composition according to any one of claims 1 to 3, characterized in that The mass ratio of the low melting point glass powder to the inorganic nanomaterial is 1:(2-4); and / or, The average particle sizes of the low-melting-point glass powder and the inorganic nanomaterial are respectively 20 nm to 1000 nm.
5. The coating composition according to any one of claims 1 to 3, characterized in that It also includes an anti-settling agent and a solvent. In terms of mass percentage, the coating composition includes: 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of anti-settling agent, and 83% to 95.5% of solvent; Optionally, the anti-settling agent includes one or more of fatty alcohol polyoxyethylene ether sulfate, polyvinyl alcohol and polyacrylamide; Optionally, the solvent comprises water.
6. An anti-fogging product, characterized in that: It comprises a transparent substrate and an anti-fogging coating arranged on the surface of the transparent substrate, wherein the materials for preparing the anti-fogging coating comprise a low-melting-point glass material and an inorganic nano material in a mass ratio of 1: (1-5); Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
7. The anti-fogging product according to claim 6, characterized in that: One or more of the following conditions are met: (1) The transparent substrate comprises glass; Optionally, the melting temperature of the low-melting-point glass material is lower than the softening temperature of the glass; (2) The low melting point glass material includes one or more of a lead-based low melting point glass material, a sodium borate low melting point glass material, a potassium aluminum silicate low melting point glass material, a calcium zincate low melting point glass material and a phosphate-based low melting point glass material; (3) The inorganic nanomaterial includes one or more of solid silica nanoparticles, mesoporous silica nanoparticles, hollow silica nanospheres, silica nanosheets and diatomaceous earth; (4) The mass ratio of the low melting point glass material to the inorganic nanomaterial is 1:(2-4); (5) The anti-fogging product includes shower room glass or bathroom mirror.
8. A method for preparing an anti-fogging product, characterized in that: The steps include: Forming an anti-fogging coating on the surface of a transparent substrate to prepare an anti-fogging product; Wherein, the material for preparing the anti-fogging coating comprises a low-melting-point glass material and an inorganic nanomaterial in a mass ratio of 1: (1-5); Wherein, the melting temperature of the low-melting-point glass material is less than or equal to 650°C.
9. The method for preparing the anti-fogging product according to claim 8, characterized in that: The steps of forming an anti-fogging coating on the surface of a transparent substrate include: Obtaining a coating composition, which comprises, by mass percentage, 2% to 5% of low-melting-point glass powder, 2% to 10% of inorganic nanomaterials, 0.5% to 2% of an anti-settling agent, and 83% to 95.5% of a solvent; The coating composition is applied on the surface of the transparent substrate, the solvent is removed by heating and the low-melting-point glass powder is melted, and the anti-fogging coating is formed on the surface of the transparent substrate after cooling.
10. The method for preparing the anti-fogging product according to claim 9, characterized in that: In the step of melting the low-melting-point glass powder, the temperature is 500° C. to 700° C. and the time is 10 min to 60 min.
11. The method for preparing the anti-fogging product according to any one of claims 8 to 10, characterized in that: Before the step of forming an anti-fogging coating on the surface of the transparent substrate, the method further includes: performing a surface hydroxylation treatment on the transparent substrate.
Citation Information
Cited By
Kitchen ware and preparation method thereof
CN122229319A